Avaliação de peças resultantes de cirurgia com alça de ondas de alta frequência no colo de útero com neoplasia intraepitelial escamosa - Bittencourt, Dulcimary Dias [UNIFESP] (2010)
Objective: Evaluate the results of LETZ surgery for Cervical Intraepithelial Neoplasia (CIN). Methods: 118 patients diagnosed with severe cervical lesions were selected and submitted to loop excision of the transformation zone (LETZ). The results were evaluated by patient age, degree of lesion, number of fragments removed, state of compromise of the margins, and degree of thermal artifact. Results: Patient age varied between 17 and 55, with the average being 27; 63.6% of patients had been diagnosed with cervical intraepithelial neoplasia grade II (CIN II) and 36.4% with CIN III. The lesion was removed in one fragment in 79.6% of the cases and in two or more fragments in 20.3% of the cases. The margins were free of intraepithelial neoplasia in 85.6% of the cases, compromised in the endocervical margin in 6.8% of the cases, compromised in the ectocervical margin in 1.7% of the cases, and compromised in both margins in 3.4% of the cases. Fragment damage by artifact occurred in 2.5% of the cases, and there were no cases of fragmented material adversely affecting evaluation. The degree of artifact was light in 46.6% of the cases, moderate in 30.5 %, and serious in 22.8%. The relation between the variables shows that women who were 30 years old or more presented more cases of CIN III than those below 30 (p<0.0004). Neoplasic compromise of the surgical margins and severe grade artifact occurred more often in the cases in which two or more fragments were removed from patients who were 30 years old or more. The same was observed when the cervical lesion grade was CIN III. Conclusion: Grade III cervical intraepithelial neoplasia in women 30 years old or more when removed in two or more fragments during LETZ surgery presents a greater number of margins compromised and a more severe degree of thermal artifact.